Adequacy of treatment in outpatients with obsessive-compulsive disorder - S.E. Cohen; B.W. Storosum; N.C. Vulink; P.P. De Koning; Y. Namavar; J.B. Zantvoord; D. Denys (Comprehensive Psychiatry, 2025)
Objective: To examine whether patients with obsessive-compulsive disorder (OCD) are adequately treated with pharmacotherapy before referral to a specialized center for OCD. Methods: We performed a retrospective chart review of patients with OCD who were seen for intake at an academic outpatient center in The Netherlands between 2016 and 2023. We collected data on age, gender, illness severity using the Yale-Brown Obsessive-Compulsive Scale, duration of illness, comorbidity and past pharmacotherapy and psychotherapy. Following the international treatment guidelines, we calculated percentages of patients treated with one SSRI, two or more SSRIs, clomipramine and/or antipsychotic augmentation treatments. Using multiple regression, we analyzed if patient and illness characteristics influenced the adequacy of treatment. Results: We included 673 patients with an average YBOCS score of 27. 76 % had taken at least one SSRI, and 35 % at least two SSRIs before admission. Only 29 % received a high SSRI-dose and 4 % had taken at least two SSRIs in high dose. Clomipramine and antipsychotics augmentation had been taken by less than one-third of patients. Only 3 % of referred patients followed all guideline-recommended treatment steps. Although the vast majority of patients had received some form of psychotherapy, a minority had received exposure and response prevention treatment. Multiple regression showed that illness duration and having received psychotherapy were independent moderators of the adequacy of pharmacological treatment. Conclusion: Patients with OCD are not being treated adequately according to the pharmacological guidelines. Poor pharmacological treatment may lead to increased duration of illness, suboptimal recovery and unnecessary societal costs. Further research could clarify barriers for patients and caregivers, and facilitate improvement of pharmacological treatment for OCS.